Virulence of the Melioidosis Pathogen Burkholderia pseudomallei Requires the Oxidoreductase Membrane Protein DsbB - McMahon, Róisín M. (Infect Immun, 2018)
The naturally antibiotic-resistant bacterium Burkholderia pseudomallei is the causative agent of melioidosis, a disease with stubbornly high mortality and a complex, protracted treatment regimen. The worldwide incidence of melioidosis is likely grossly underreported, though it is known to be highly endemic in northern Australia and Southeast Asia. Bacterial disulfide bond (DSB) proteins catalyze the oxidative folding and isomerization of disulfide bonds in substrate proteins. In the present study, we demonstrate that B. pseudomallei membrane protein disulfide bond protein B (BpsDsbB) forms a functional redox relay with the previously characterized virulence mediator B. pseudomallei disulfide bond protein A (BpsDsbA). Genomic analysis of diverse B. pseudomallei clinical isolates demonstrated that dsbB is a highly conserved core gene. Critically, we show that DsbB is required for virulence in B. pseudomallei. A panel of B. pseudomallei dsbB deletion strains (K96243, 576, MSHR2511, MSHR0305b, and MSHR5858) were phenotypically diverse according to the results of in vitro assays that assess hallmarks of virulence. Irrespective of their in vitro virulence phenotypes, two deletion strains were attenuated in a BALB/c mouse model of infection. A crystal structure of a DsbB-derived peptide complexed with BpsDsbA provides the first molecular characterization of their interaction. This work contributes to our broader understanding of DSB redox biology and will support the design of antimicrobial drugs active against this important family of bacterial virulence targets.